Jesus in the Latin Talmud : Judaism and Christianity during the Disputation of Paris in 1240 and Other Transcultural Issues - Bo, Federico Dal (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2025., 2024)
Between 1238 and 1239, the notorious Jewish convert Nicholas Donin persuaded Pope Gregory IX to condemn the Talmud, prompting European kings to intervene. Only King Louis IX of France agreed to a public disputation in 1240, subjecting the Talmud to scrutiny. Prominent Jewish and Christian figures debated Jesus in the Talmud. The Talmud was condemned between 1241 and 1242, but the Church of Paris, responding to Jewish pleas, allowed an appeal. Scholars were commissioned to translate portions of the Talmud, resulting in two anthologies titled Extractiones de Talmud-the first translation of this work. Still, this did not save the Talmud from burning.